Influence Of Intellectual Capıtal And Good Corporate Governance Mechanısm On Bankıng Fınancıal Performance - Wachidah Fauziyanti; Harjum Muharam (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this study was to analyze the effect of intellectual capital and good corporate governance mechnisms on banking financial performance. The population of this study are banks listed on the Indonesia Stock Exchange 2018-2022. The sampe in this study used purposive sampling and the number of samples was 32 banks in the 2018-2020 observation period. The data ini this study uses secondary data taken from the annual banking reports published on the Indonesia Stock Exchange. The analysis technique used in this research is multipe linear regression. The analysis test result show the t-test result that the variable intellectual capital proxied by structural capital efficiency has a positive effect on financial performance as proxied by Return On Assets. Meanwhile, the mechanism of good corporate governance proxied by independent commissioners and institusional ownership also has a positive effect on return on assets as a proxy for financial performance